FROM RETRIBUTION TO RESTORATION: INTEGRATING BANKRUPTCY MECHANISMS INTO INDONESIAN CORPORATE CRIMINAL LIABILITY - Ricki Pratama; Yuliati Yuliati; Abdul Madjid (Universitas Syiah Kuala, 2026)
The ineffectiveness of existing mechanisms for recovering victim losses has been contested in Indonesian criminal law. The New Criminal Code stipulates additional penalties like compensation; however, there is a lack of clear execution guidelines, often resulting in